Analysis Of Mechanical Properties SMAW (Shielded Metal Arc Welding) Welding Joints Of Portable Electric Hydraulic Jack Frame - Wisnujati, Andika; Andryansyah, Juni (INTEK: Jurnal Penelitian, 2020)
Welding is a very important part of the development and growth of the industry because it has a role in engineering, reparation, and construction. Shielded   Metal   Arc Welding (SMAW) or the conventional arc welding   process is particularly dominant in structural joints, pressure vessels and in maintenance and repair work. In welding, different metals are joined economically and at a much faster rate as compared with other fabrication processes like riveting and casting. The purpose of this research is to find out the cooling media cooler against SMAW smelter tensile strength by using the E6013 electrode. This study uses low carbon steel material that has levels Fe = 98,3%; C = 0,30%, Si = 0,23%. The material is given 75A welding current with cooling variation on the connection result using oil, water, and room temperature. The highest tensile stress value obtained in the oil cooling treatment was 844,76 N/mm2, the highest strain value was obtained on the raw materials of 16%, the highest elasticity value was obtained in the oil cooling treatment of 703.96 N/mm2. According to the research results can be concluded that the variations of cooling media greatly affect the strength of the welding connection.